Effect of video training on anxiety and knowledge level among caregivers of children and adolescents chemotherapy: A randomized clinical trial - Silmara de Oliveira Silva; Naryllenne Maciel de Araújo; Nahadja Tahaynara Barros Leal; Mariane Elivânia Silva; Kauanny Vitoria Gurgel dos Santos; Tâmara Taynah Medeiros da Silva; Jucielly Ferreira da Fonseca; Katia Regina Barros Ribeiro; Rodrigo Assis Neves Dantas; Daniele Vieira Dantas (iScience)
Summary: This study aimed to evaluate the effect of video training compared to verbal guidelines for acquiring knowledge and reducing anxiety in caregivers of children and adolescents undergoing chemotherapy. A randomized, controlled, double-blind, two-arm clinical trial with simple randomization was carried out. 26 caregivers of children and adolescents recently diagnosed with cancer participated in the study, who were randomly assigned to the experimental group, who received verbal guidance associated with an educational technology in video format about the chemotherapy process; or to the control group, which received only verbal instructions. Patients in the experimental group showed better performance in answering the questions correctly. Caregivers in the experimental group showed a reduction in State-Trait Anxiety Inventory (STAI)-State when comparing the initial period with the final period with value (95% confidence interval [CI]; p < 0.05).